2005
DOI: 10.2188/jea.15.s9
|View full text |Cite
|
Sign up to set email alerts
|

Reproducibility and Validity of a Self-administered Food Frequency Questionnaire Used in the JACC Study

Abstract: BACKGROUND: A self-administered questionnaire on dietary habits used in the JACC Study contained a 40-item food frequency questionnaire (FFQ). Although more than 110 thousand subjects enrolled in JACC Study and responded to the FFQ, no validation study has been conducted to date. METHODS: Eighty-five volunteers among the cohort members completed 2 FFQs (FFQs 1&2) and 12-day weighed dietary records (WDR). The interval between the two FFQs was one year. During the one year, the subjects carried out a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
150
2

Year Published

2007
2007
2023
2023

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 134 publications
(170 citation statements)
references
References 8 publications
13
150
2
Order By: Relevance
“…Several Latin American (Rodriguez et al, 2002;Bautista et al, 2005) and European (Johansson et al, 2002) studies also presented validities with a similar range of correlation of coefficient. In the Asian region, validation studies for Japanese cohort studies showed correlation coefficients of nutrient intakes ranged from 0.13 to 0.81, and their observed median was 0.3-0.4, which are similar to our results (Egami et al, 1999;Tsubono et al, 2001;Ogawa et al, 2003;Tsugane et al, 2003;Date et al, 2005). The Chinese study reported higher correlation coefficients (0.41-0.66) than the Japanese study in validity (Shu et al, 2004).…”
Section: Discussionsupporting
confidence: 88%
“…Several Latin American (Rodriguez et al, 2002;Bautista et al, 2005) and European (Johansson et al, 2002) studies also presented validities with a similar range of correlation of coefficient. In the Asian region, validation studies for Japanese cohort studies showed correlation coefficients of nutrient intakes ranged from 0.13 to 0.81, and their observed median was 0.3-0.4, which are similar to our results (Egami et al, 1999;Tsubono et al, 2001;Ogawa et al, 2003;Tsugane et al, 2003;Date et al, 2005). The Chinese study reported higher correlation coefficients (0.41-0.66) than the Japanese study in validity (Shu et al, 2004).…”
Section: Discussionsupporting
confidence: 88%
“…The dietary component of the questionnaire included 40 food items (33). For 33 foods or dishes, we asked about the average intake frequency without specifying portion size information.…”
Section: Methodsmentioning
confidence: 99%
“…with previous developed FFQ in Korea (11,17,18) and other countries (4,9,10,22) . The main reduction from the initial 993 dishes compiled in the 24 h recall to the ninety-five dishes in the FFQ resulted from aggregating 359 items to ninety-five usable dishes in the last step.…”
Section: Discussionmentioning
confidence: 53%